Journals of Expeditions of Discovery into Central Australia and Overland from Adelaide to King George's Sound in the Years 1840-1: Sent By the Colonists of South Australia, with the Sanction and Support of the Government: Including an Account of the Manners and Customs of the Aborigines and the State of Their Relations with Europeans $1 (BCompletes - Eyre, Edward John, 1815-1901 (Salt Lake City, UT : Project Gutenberg, 2004)
"Journals of Expeditions of Discovery into Central Australia and Overland from..." by Edward John Eyre is a travelogue published in 1845. This account chronicles Eyre's year-long expedition from Adelaide into Australia's uncharted interior, documenting the harsh landscapes, scarce resources, and encounters with Aboriginal peoples. Written in epistolary form during his voyage to London, the work combines adventure narrative with observations on Aboriginal customs and colonial relations, establishing Eyre's reputation as one of early Australia's notable explorers. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Journals_of_Expeditions_of_Discovery_into_Central_Australia
Release date is 2004-03-01
Produced by Col Choat
Keywords: Australia -- Discovery and exploration; Ethnology -- Australia